2011
DOI: 10.1007/s00192-011-1447-7
|View full text |Cite
|
Sign up to set email alerts
|

Continent women have better urethral neuromuscular function than those with stress incontinence

Abstract: Introduction and hypothesis The objective of this study is to describe urethral neuromuscular function using concentric needle electromyography (EMG) in stress incontinent (SUI) and asymptomatic women. Methods Following Institutional Review Board approval, we recruited SUI and asymptomatic women without urinary incontinence. Participants underwent quantitative urethral EMG and urodynamic testing. Results Sixty-seven women (37 SUI, 30 continent) with mean±SD age of 44±12 years participated. Nearly all EMG p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…More detailed histological descriptions are needed that include different types of collagen, decorin, biglycan, aggrecan, and other possible constituents that may form this particular enthesis . Investigation of the nerve supply to this region might also be worthwhile, since pudendal nerve damage has been noted in women with pelvic floor dysfunction . Finally, a traction force was applied to the top of the perineal body of a cadaveric hemipelvis in an attempt to show deformed pattern of the levator ani by increased intra‐abdominal pressure.…”
Section: Discussionmentioning
confidence: 99%
“…More detailed histological descriptions are needed that include different types of collagen, decorin, biglycan, aggrecan, and other possible constituents that may form this particular enthesis . Investigation of the nerve supply to this region might also be worthwhile, since pudendal nerve damage has been noted in women with pelvic floor dysfunction . Finally, a traction force was applied to the top of the perineal body of a cadaveric hemipelvis in an attempt to show deformed pattern of the levator ani by increased intra‐abdominal pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In imaging studies, the striated urethral sphincter has been found to be smaller in women with SUI compared to continent controls [7,8]. In EMG studies, the striated urethral sphincters of women with SUI demonstrated smaller EMG amplitudes and shorter motor-unit-potential durations with more phases than do continent controls [9,10], indicating primarily myogenic changes.…”
Section: Introductionmentioning
confidence: 95%
“…These studies have shown that there is a neurogenic basis for stress incontinence [1] and uterovaginal prolapse [2] caused by vaginal delivery as well as other associated factors of weakness of the pelvic floor muscles and connective tissue. A study by Kenton et al [3] again confirms the value of neurological investigations in the study of pelvic floor disorders. Using concentric needle electromyography, they showed that women with stress incontinence had poorer urethral innervation than continent controls.…”
mentioning
confidence: 76%